Maternity leave and its consequences for subsequent careers in Germany - Nele Franz (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2014)
Subject of this paper is the investigation of wage developments of women interrupting their careers for giving birth tochildren in comparison to men's wages not facing a parental interruption. We estimate OLS regression models for different subcategories defined by age and point in time. We use data from the German Socioeconomic Panel from 1984 to 2011 to show the importance of legal job protection on reentry wages. Furthermore, we show that wages and the penalty for maternity differs by the duration of interruption as well as in short-, intermediate and long-run perspective. We find less wage penalty for women interrupting their careers within legal protection in the short run, but delayed compensating penalties for the same group in the long run.
Keywords: C21; J13; J24; J31; 330; human capital; parental leave; wages; OLS